Examining the day-of-the-week-effect and the-month-of-the-year-effect in cryptocurrency market - Robiyanto Robiyanto; Yosua Arif Susanto; Rihfenti Ernayani (Jurnal Keuangan dan Perbankan, 2019)
Cryptocurrency market is an attractive field for researchers in finance nowadays. One topic that can be studied is related to the existence of anomalies in the cryptocurrency market. This research was conducted to examine whether the cryptocurrency market, especially on Bitcoin and Litecoin, has day-of-the-week and month-of-the-year effects. The Bitcoin and Litecoin were used as objects because they were a cryptocurrency with a large market capitalization. The data used were monthly cryptocurrency returns for examining the month-of-the-year-effect and daily returns for examining the day-of-the-week-effect from 2014-2018. GARCH (1,1) analysis was done to see these effects on the cryptocurrency market. The results indicate that the phenomena of day-of-the-week and month-of-the-year effect existed in the cryptocurrency market. Therefore, the cryptocurrency market was not an efficient market. The pattern in the Bitcoin and Litecoin could later be utilized by investors. The investors should buy Bitcoin at the end of January and they should sell them at the end of February. While, for the investors who traded daily, can trade Bitcoin in Monday, Wednesday and Thursday because in these days, the Bitcoin have the potential to generate daily profits.JEL Classification: G14, G19DOI: https://doi.org/10.26905/jkdp.v23i3.3005